Analysing Information Retrieval Strategies in Library and Food Sciences (International Journal of Food and Nutritional Sciences, 2022)
This paper explores the intersection of library science and food science by analysing information retrieval strategies employed in both disciplines. Information retrieval plays a crucial role in gathering and accessing relevant knowledge in library science and food science research. This study aims to compare and contrast the information retrieval practices, challenges, and tools used in these two fields. Through a comparative analysis, the paper identifies effective strategies in information retrieval and offers recommendations for integrating successful library science approaches into food science research. The findings provide insights for researchers and practitioners in both disciplines to enhance their information retrieval methods and advance their respective fields.